2019
DOI: 10.1002/mbo3.902
|View full text |Cite
|
Sign up to set email alerts
|

Expression of different ParE toxins results in conserved phenotypes with distinguishable classes of toxicity

Abstract: Toxin-antitoxin (TA) systems are found on both chromosomes and plasmids. These systems are unique in that they can confer both fatal and protective effects on bacterial cells-a quality that could potentially be harnessed given further understanding of these TA mechanisms. The current work focuses on the ParE subfamily, which is found throughout proteobacteria and has a sequence identity on average of approximately 12% (similarity at 30%-80%). Our aim is to evaluate the equivalency of chromosomally derived ParE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 76 publications
0
13
0
Order By: Relevance
“…Antitoxin contacts deduced from superposition of the AtYoeB structure (PDB ID 6N90) onto the E. coli YoeB-YefM complex (PDB ID 2A6Q) (Kamada and Hanaoka, 2005). more than 10 h of overexpression (Ames et al, 2019). We are able to produce recombinant AtYoeB in the absence of antitoxin with yields of 3-5 milligrams per liter of culture, and with greater than 7 milligrams per liter of culture when the antitoxin is co-expressed (see Materials and Methods section for induction details).…”
Section: Atyoeb Is Toxic To Agrobacterium But Not Escherichia Culturesmentioning
confidence: 99%
“…Antitoxin contacts deduced from superposition of the AtYoeB structure (PDB ID 6N90) onto the E. coli YoeB-YefM complex (PDB ID 2A6Q) (Kamada and Hanaoka, 2005). more than 10 h of overexpression (Ames et al, 2019). We are able to produce recombinant AtYoeB in the absence of antitoxin with yields of 3-5 milligrams per liter of culture, and with greater than 7 milligrams per liter of culture when the antitoxin is co-expressed (see Materials and Methods section for induction details).…”
Section: Atyoeb Is Toxic To Agrobacterium But Not Escherichia Culturesmentioning
confidence: 99%
“…We have previously measured the toxicity of AtYoeB to E. coli and noted a delayed impact on colony forming units, with minimal impact on existing cells until more than ten hours of overexpression. [63] AtYoeB in the absence of antitoxin could reproducibly yield 3-5 milligrams per liter of LB culture, and with greater than 7 milligrams per liter of culture when the antitoxin is co-expressed (see Methods section for induction details).…”
Section: Resultsmentioning
confidence: 99%
“…This superfamily contains toxins that assume a similar fold, although three different biochemical activities have been described for their members. Toxins of the RelE family (including YafQ and YoeB) inhibit translation by mRNA cleavage (Harms et al, 2018), toxins of the ParE family have been reported to interfere with DNA replication by inhibiting gyrase (Ames et al, 2019), and the Vibrio parahaemolyticus toxin Vp1843 has been shown to have a DNA nicking endonuclease activity (Zhang et al, 2017).…”
Section: Discussionmentioning
confidence: 99%